YOGYAKARTA AIR BORNE QUALITY BASED ON THE LEAD PARTICULATE CONCENTRATION - Zaenal Abidin; Sunardi Sunardi (Indonesian Journal of Chemistry, 2009)
Analysis of Yogyakarta air quality based on concentration of lead particulate using Fast Neutron Activation Analysis (FNAA) method has been done. The sample was taken 3 times in 16 strategic locations of Yogyakarta city using Hi-Vol air sampler that equipped with cellulose filter TFA 2133. The sample irradiated for 30 min with 14 MeV fast neutron and then counted using gamma spectroscopy (AccuSpec). The result indicated that concentration of Pb-208 along Diponegoro street up to Janti street respectively are minimally (0.689 - 0.775) mg/m3, and maximally:  (1.598 - 1.785) mg/m3. According to DIY governor decree No. 153/2002 about the limited toxicity ambient on Yogyakarta area it is concentration that Pb. The concentration of Pb-208 are still below the permitted value of 2 mg/m3, but in certain areas, the Pb concentration is almost equal to upper limit of permitted concentration of Pb.